Implementing injury prevention training in youth handball (I-PROTECT) in Sweden: study protocol for a cluster randomised trial - Per Nilsen; Alex Donaldson; Eva Ageberg; Sofia Bunke; Jennie Linnéll; Karin Moesch; Karolina Lucander; Axel Ström; Robert Wedberg; Per Ekberg (BMJ Public Health)
Introduction Efficacy trials show that evidence-based injury prevention training reduces injuries in youth athletes but effectiveness, that is, outside the controlled setting, is lower and, consequently this training has had limited public health impact. Insufficient involvement of end-users at the individual and organisational levels is identified as a main barrier to successful implementation. The ‘Implementing injury Prevention training ROutines in TEams and Clubs in youth Team handball (I-PROTECT)’ uses an ecological participatory design incorporating the perspectives of multiple stakeholders throughout the project. Within the I-PROTECT research project, the specific aim of this study is to investigate the implementation of the end-user-targeted I-PROTECT programme.Methods and analysis This pragmatic two-armed cluster randomised controlled trial is conducted collaboratively with the Swedish Handball Federation that has overall responsibility for handball in Sweden. Randomly selected clubs in Sweden offering handball for both female and male youth players are invited to participate. 18 clubs are randomised (stratified by club size) to intervention (I-PROTECT plus tailored implementation support) or control (injury prevention programme currently available through the Swedish Handball Federation). The anticipated total number of potential participants (players, coaches, club administrators, parents/guardians) is ~3500. The I-PROTECT programme includes end-user-targeted information and physical and psychological injury prevention training available in a specifically developed interactive mobile application. Implementation strategies were selected from the Expert Recommendations for Implementing Change discrete implementation strategy compilation, based on feedback from end-users. Implementation outcomes will be investigated at the end of the handball season using the Reach, Effectiveness, Adoption, Implementation and Maintenance implementation evaluation framework. A study-specific questionnaire, app downloads and/or workshops will be used to collect data.Ethics and dissemination The Swedish Ethical Review Authority approved the study. Results will be disseminated in peer-reviewed scientific journals, as popular science articles, at international conferences and communicated via the Swedish Handball Federation.Trial registration number NCT05696119.